2022
DOI: 10.47176/jafm.15.01.32901
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction Characteristics of Bionic Structure Composed of Grooves and Mucous Membrane Acting on Turbulent Boundary Layer

Abstract: The biological surface structure comprising fish scales and a mucous membrane exhibits good turbulent drag reduction ability. Based on this structure, a bionic frictional drag reduction model composed of a grooved structure and mucous membrane was established herein, and its efficacy in reducing the resistance of a turbulent boundary layer was analyzed. Accordingly, the drag reduction performance of the bionic structure was investigated through large eddy simulations. The results revealed that the mucous membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, he concluded that menhaden use mechanical sieving to retain particles on the branchiospinules. Another productive future approach could be to incorporate synthetic hydrogels and other mucus analogues (e.g., Authimoolam and Dziubla, 2016;Bej and Haag, 2022) into computational models as done with drag-reducing agents and microgrooves (Zhang et al, 2022a), or into physical models as suggested by Witkop et al (2023).…”
Section: A B Cmentioning
confidence: 99%
“…Therefore, he concluded that menhaden use mechanical sieving to retain particles on the branchiospinules. Another productive future approach could be to incorporate synthetic hydrogels and other mucus analogues (e.g., Authimoolam and Dziubla, 2016;Bej and Haag, 2022) into computational models as done with drag-reducing agents and microgrooves (Zhang et al, 2022a), or into physical models as suggested by Witkop et al (2023).…”
Section: A B Cmentioning
confidence: 99%
“…Research shows that the aerodynamics of PEHs can be changed by changing its surface structure, and its vibration mode can be signi cantly affected, thus improving its performance [30]. Zhang et al [31] studied the sh scale shape of the groove surface structure, designed its shape, and visually displayed the in uence of the structure on turbulence. Yang et al [32] studied the in uence and control of non-smooth body structure on vehicle tail vortex.…”
Section: Introductionmentioning
confidence: 99%